2018
DOI: 10.1242/jeb.171728
|View full text |Cite
|
Sign up to set email alerts
|

Responses to mechanically and visually cued water waves in the nervous system of the medicinal leech

Abstract: Sensitivity to water waves is a key modality by which aquatic predators can detect and localize their prey. For one such predatorthe medicinal leech, Hirudo verbana -behavioral responses to visual and mechanical cues from water waves are well documented. Here, we quantitatively characterized the response patterns of a multisensory interneuron, the S cell, to mechanically and visually cued water waves. As a function of frequency, the response profile of the S cell replicated key features of the behavioral prey … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Leeches are efficient predators because of their specialized predation adaptation, with acute senses such as hearing, vision, and chemosensation. Leeches trace and locate their prey via mechanical and visual cues from water waves on the basis of S cells [ 9 ]. Ethological experiments have shown that leeches can quickly identify and locate the source of sound by analyzing the distribution of water waves [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leeches are efficient predators because of their specialized predation adaptation, with acute senses such as hearing, vision, and chemosensation. Leeches trace and locate their prey via mechanical and visual cues from water waves on the basis of S cells [ 9 ]. Ethological experiments have shown that leeches can quickly identify and locate the source of sound by analyzing the distribution of water waves [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leeches trace and locate their prey via mechanical and visual cues from water waves on the basis of S cells [ 9 ]. Ethological experiments have shown that leeches can quickly identify and locate the source of sound by analyzing the distribution of water waves [ 9 ]. Among hearing-related genes, SIX1 mediates the relative numbers of sensory hair cells and statoacoustic ganglion neurons [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates that its visual system has the ability to process spatiotemporal patterned visual stimuli, despite the lack of image-forming eyes. S cells respond when the leech is presented with flashes of light as well as to stimuli associated with water waves (Lehmkuhl et al, 2018). Their multimodal response properties, along with the fact that the S-cell system spans the entire body, make them an intriguing candidate for further investigations.…”
Section: Introductionmentioning
confidence: 99%